High-Performance Vertical Light-Emitting Transistors Based on ZnO Transistor/Quantum-Dot Light-Emitting Diode Integration and Electron Injection Layer Modification - Jui-Fen Chang; Jia-Min Yu (Micromachines, 2023)
Vertical light-emitting transistors (VLETs) consisting of vertically stacked unipolar transistors and organic light-emitting diodes (OLEDs) have been proposed as a prospective building block for display technologies. In addition to OLEDs, quantum-dot (QD) LEDs (QLEDs) with high brightness and high color purity have also become attractive light-emitting devices for display applications. However, few studies have attempted to integrate QLEDs into VLETs, as this not only involves technical issues such as compatible solution process of QDs and fine patterning of electrodes in multilayer stacked geometries but also requires a high driving current that is demanding on transistor design. Here we show that these integration issues of QLEDs can be addressed by using inorganic transistors with robust processability and high mobility, such as the studied ZnO transistor, which facilitates simple fabrication of QD VLETs (QVLETs) with efficient emission in the patterned channel area, suitable for high-resolution display applications. We perform a detailed optimization of QVLET by modifying ZnO:polyethylenimine nanocomposite as the electron injection layer (EIL) between the integrated ZnO transistor/QLED, and achieve the highest external quantum efficiency of ~3% and uniform emission in the patterned transistor channel. Furthermore, combined with a systematic study of corresponding QLEDs, electron-only diodes, and electroluminescence images, we provide a deeper understanding of the effect of EIL modification on current balance and distribution, and thus on QVLET performance.